A reimagining of history based on the Novel The Harmony Silk Factory by Tash Aw - Lajiman Janoory,; Mohammad Sidik Ariffin,; Mazura@Mastura Muhammad, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This article analyses the text, The Harmony Silk Factory, by Tash Aw and employs the novel to negate the idea of history as scientific and stable depiction of reality. The text specifically focuses on the central character, Johnny Lim, and utilises the character as an analogy to the act of historical writing. The article hypothesises that historical writing is an intellectual production with strong fictional elements embedded into it. The article also frames its argument based on ideas elucidated by Beverly Southgate about the fictional nature of history and the historical nature of fiction. The frame of argument presupposes that historical narration has more similarity to fictional writing than previously assumed. By analysing the central character in the novel and utilising him to symbolise our conception of history, the research strives to demystify the idea of history as scientific and objective narrative of our historical reality. The research concludes that the novel by Tash Aw can be considered as metaphorical allusions to the idea of history. The implication of the research allows us to view historical texts much more critically due to the inability of historians to write objectively and authentically about history/reality.